2019
DOI: 10.1093/biosci/biz069
|View full text |Cite
|
Sign up to set email alerts
|

Smaller Classes Promote Equitable Student Participation in STEM

Abstract: As science, technology, engineering, and mathematics (STEM) classrooms in higher education transition from lecturing to active learning, the frequency of student interactions in class increases. Previous research documents a gender bias in participation, with women participating less than would be expected on the basis of their numeric proportions. In the present study, we asked which attributes of the learning environment contribute to decreased female participation: the abundance of in-class interactions, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 45 publications
4
47
0
Order By: Relevance
“…This complements the findings of a study that saw female participation go down after transitioning from an all-girls school to mixed-sex education (Canada and Pringle, 1995), but to our knowledge, this is the first time this effect has been shown in biology courses specifically. Perhaps we saw this when other studies did not simply because we had more variance in our attendance ratios than past studies (Eddy et al, 2014;Ballen et al, 2017Ballen et al, , 2019. It is also possible that having female peers is more important for female students in more conservative populations.…”
Section: Participation (Research Questions 1 and 2)mentioning
confidence: 85%
See 3 more Smart Citations
“…This complements the findings of a study that saw female participation go down after transitioning from an all-girls school to mixed-sex education (Canada and Pringle, 1995), but to our knowledge, this is the first time this effect has been shown in biology courses specifically. Perhaps we saw this when other studies did not simply because we had more variance in our attendance ratios than past studies (Eddy et al, 2014;Ballen et al, 2017Ballen et al, , 2019. It is also possible that having female peers is more important for female students in more conservative populations.…”
Section: Participation (Research Questions 1 and 2)mentioning
confidence: 85%
“…Course level, class size, and instructor gender were not significant predictors of participation gaps in our population. Eddy et al (2014) and Ballen et al (2019) similarly found no effect of instructor gender on participation gender gaps. Interestingly, we did see significantly more participation overall in female-instructed classrooms (unpublished data), but this had no impact on the participation gender gap, because male and female students were both more likely to participate with a female instructor.…”
Section: Participation (Research Questions 1 and 2)mentioning
confidence: 93%
See 2 more Smart Citations
“…Eddy et al [47] observed substantially lower classroom participation in-person among women compared to men. Subsequent studies in the context of in-person courses have documented gender differences in student comfort participating in front of the whole class [76], lower likelihood of women participating in larger classes [77], student perception of their own intelligence when comparing it to others [78], and preference for working with a friend in small group work [76]. Such differences not only represent missed learning opportunities for women to participate but can also perpetuate stereotypes about men being smarter or more capable in science.…”
Section: Explanationsmentioning
confidence: 99%